Reconstruction of displaced acromio-clavicular joint dislocations using a triple suture-cerclage: description of a safe and efficient surgical technique - Sandmann Gunther H; Martetschläger Frank; Mey Lisa; Kraus Tobias M; Buchholz Arne; Ahrens Philipp; Stöckle Ulrich; Freude Thomas; Siebenlist Sebastian (Patient Safety in Surgery, 2012)
Abstract Purpose In this retrospective study we investigated the clinical and radiological outcome after operative treatment of acute Rockwood III-V injuries of the AC-joint using two acromioclavicular (AC) cerclages and one coracoclavicular (CC) cerclage with resorbable sutures. Methods Between 2007 and 2009 a total of 39 patients fit the inclusion criteria after operative treatment of acute AC joint dislocation. All patients underwent open reduction and anatomic reconstruction of the AC and CC-ligaments using PDS® sutures (Polydioxane, Ethicon, Norderstedt, Germany). Thirty-three patients could be investigated at a mean follow up of 32±9 months (range 24–56 months). Results The mean Constant score was 94.3±7.1 (range 73–100) with an age and gender correlated score of 104.2%±6.9 (88-123%). The DASH score (mean 3.46±6.6 points), the ASES score (94.6±9.7points) and the Visual Analogue Scale (mean 0.5±0,6) revealed a good to excellent clinical outcome. The difference in the coracoclavicular distance compared to the contralateral side was <5 mm for 28 patients, between 5-10 mm for 4 patients, and more than 10 mm for another patient. In the axial view, the anterior border of the clavicle was within 1 cm (ventral-dorsal direction) of the anterior rim of the acromion in 28 patients (85%). Re-dislocations occured in three patients (9%). Conclusion Open AC joint reconstruction using AC and CC PDS cerclages provides good to excellent clinical results in the majority of cases. However, radiographically, the CC distance increased significantly at final follow up, but neither the amount of re-dislocation nor calcifications of the CC ligaments or osteoarthritis of the AC joint had significant influence on the outcome. Level of evidence Case series, Level IV